Perspektif Pendidikan Islam dalam Kitab Waṣaya Al Aba’ Lil Abna’ untuk Membentuk Karakter Santri - Lailatul Shofiyah; Jauharu Ma’arif; Aya Mamu’ah (Fakultas Tarbiyah Institut Pesantren Sunan Drajat Lamongan, 2023)
The perspective of Islamic education in the study of the book Waṣãyã Al Ãbã' Lil Abnã' to shape the character of the students, where in the study of the book explains about manners which are transformed into advice about morality. Knowing How the Concept and Implementation of Islamic Education in the Book